Values and Norms Matter: Ketidakikutsertaan Indonesia dalam Regional Cooperation Agreement on Combating Piracy and Armed Robbery against Ships (ReCAAP) - Mayora Bunga Swastika (Universitas Diponegoro, 2018)
This article examines Indonesia’s choice to not join the Regional Cooperation Agreement on Combating Piracy and Armed Robbery against Ships in Asia (ReCAAP). Piracy is a transnational crime that requires cooperation to deal with. Asian waters has a high level of piracy, especially in the Malacca Strait and Indonesian Waters. ReCAAP, as a regional institution, was formed to deal with piracy and armed robbery against ships in Asian waters. Indonesia has been choosing not to join ReCAAP to combat piracy and armed robbery against ships. The purpose of this article is to explain the causes of Indonesia’s rejection to join ReCAAP. This article uses literature study by collecting related data piracy in the Malacca Strait and Indonesian waters. Beside, this article collecting related data about Indonesia foreign policy. In the end, this article shows there are non-material factors that influencing Indonesia’s behavior not to join ReCAAP. The non-material factors are historical, values, and norms.Keywords: Indonesia, piracy, Malacca Strait, maritime cooperation, ReCAAP, values, norms